Epstein-Barr Virus and Multiple Sclerosis - Houen, Gunnar; Trier, Nicole Hartwig; Frederiksen, Jette Lautrup (Frontiers in Immunology, 2020)
Multiple sclerosis (MS) is a neurologic disease affecting myelinated nerves in the central nervous system (CNS). The disease often debuts as a clinically isolated syndrome, e.g. optic neuritis (ON), which later develops into relapsing-remitting (RR) MS, with temporal attacks or primary progressive (PP) MS. Characteristic features of MS are inflammatory foci in the CNS and intrathecal synthesis of immunoglobulins (Igs), measured as an IgG index, oligoclonal bands (OCBs) or specific antibody indexes. Major predisposing factors for MS are certain tissue types (e.g. HLA DRB1*15:01), vitamin D deficiency, smoking, obesity and infection with Epstein-Barr Virus (EBV). Many of the clinical signs of MS described above can be explained by chronic/recurrent EBV infection and current models of EBV involvement suggest that RRMS may be caused by repeated entry of EBV-transformed B cells to the CNS in connection with attacks while PPMS may be caused by more chronic activity of EBV-transformed B cells in the CNS. In line with the model of EBV’s role in MS, new treatments based on monoclonal antibodies (MAbs) targeting B cells have shown good efficacy in clinical trials both for RRMS and PPMS, while MAbs inhibiting B cell mobilization and entry to the CNS have shown efficacy in RRMS. Thus, these agents, which are now first line therapy in many patients, may be hypothesized to function by counteracting a chronic EBV infection.